Digital health literacy and COVID-19 pandemic: Results of a nationwide survey in Germany. (20th October 2021) - De Santis, KK; Jahnel, T; Sina, E; Wienert, J; Zeeb, H
Abstract: Background: Digital health literacy is important for interpreting information and making health decisions in an increasingly digitised world. We investigated the perceived digital health literacy and the attitudes towards digital information on the COVID-19 pandemic using a nationwide survey. Methods: We conducted a cross-sectional, computer-assisted telephone survey in October 2020 using a panel sample of Internet users selected from the general population living in Germany. Responses on items regarding the COVID-19 pandemic and the eHealth Literacy Scale (eHEALS; total sum score of 8=minimum to 40=maximum perceived digital health literacy) were analysed using descriptive statistics and a linear regression analysis. Results: Of the 1014 Internet users, 928 (92%) completed the eHEALS. The respondents were 52% female, aged 14-93 years (mean±SD of 55±17 years), 66% with up to secondary education and 45% with up to average household income. The responses on eHEALS were consistent (Cronbach's α=.88). While the perceived digital health literacy was high (mean±SD eHEALS score of 31±6), less than half of respondents (43%) were confident in using digital information for health decisions. Higher digital health literacy was associated with younger age (β=-.22, p<.001), higher household income (β=.21, p<.001) and more education (β=.14, p<.001). About half of respondents (52%) reported that they sometimes or often come across inaccurate digital information on the COVID-19 pandemic. The majority (78%) were confident in their ability to recognise inaccurate digital information on the COVID-19 pandemic and 43% installed the contact-tracing app. Discussion: Internet users in Germany report high perceived digital health literacy but low confidence in making health decisions and low trust in digital information on the COVID-19 pandemic. Factors contributing to such low confidence in the general population need to be investigated. Key messages: Despite high digital health literacy, the confidence in making health decisions is low in the general public. The trust in digital information on the COVID-19 pandemic is low.